Students' Perception of Anxiety in Learning Speaking at Students Higher Education - Andestina, Dini Eka (Langue (Journal of Language and Education), 2024)
This study investigates students’ anxiety in learning to speak English at State Islamic University Sulthan Thaha Saifuddin Jambi. It aimed to identify the factors contributing to students’ anxiety in speaking. A case study design was employed, involving five participants—two males and three females—who were selected using purposive sampling based on specific criteria. Data were collected through online interviews and analyzed descriptively to answer the research question. The findings revealed four key factors contributing to students’ speaking anxiety: lack of confidence, limited vocabulary, pronunciation difficulties, and fear of making mistakes.